Pengaruh Penerapan Pembayaran Qris Terhadap Kepuasan Mahasiswa Pujasera Politeknik Negeri Bandung - Muhammad Fikri Fadhilah (International Journal Administration, Business & Organization, 2023)
This research aims to evaluate the impact of using the QRIS payment method on the level of satisfaction of students who shop at the Bandung State Polytechnic Pujasera, Indonesia. This research uses a quantitative descriptive approach where data is obtained by distributing questionnaires to students of the Bandung State Polytechnic, Indonesia who regularly shop at Pujasera. The questionnaire was distributed via the Google Form platform, and the number of respondents involved was 112 people. The data analysis process includes validity tests, reliability tests, normality tests, and the application of simple linear regression. The research results show that the use of payments via QRIS has a significant impact on the level of satisfaction of students who shop at the Bandung State Polytechnic Pujasera, Indonesia.